2022
DOI: 10.1111/liv.15293
|View full text |Cite
|
Sign up to set email alerts
|

Sex is a major effect modifier between body composition and mortality in patients with cirrhosis assessed for liver transplantation

Abstract: Background and Aims: Body composition predicts mortality in patients with cirrhosis.The impact of sex on this association is unknown. We investigated the impact of sex on this association in patients with cirrhosis assessed for liver transplantation.Methods: This single-centre retrospective cohort study included adults assessed for liver transplantation. Nutritional status was assessed using the Royal Free Hospital-Global Assessment (RFH-GA). Body composition at the third lumbar vertebrae was determined. Sarco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Two entries by Kim et al ( 24 , 29 ) applied the sarcopenia index, that is, the ratio of total appendicular skeletal muscle mass (kg) to body mass index (kg/m 2 ), using consistent cutoffs of <0.789 for men and <0.521 for women. Two sarcopenia entries Resulted from muscle deficits estimated by the psoas muscle index of L3 ( 32 , 35 ). Finally, a single prevalence entry was derived from the construct used by ( 37 ), namely, a paraspinal muscle index deficiency, diagnosed on values <12.62 cm 2 /m 2 for men and <9.77 cm 2 /m 2 for women.…”
Section: Resultsmentioning
confidence: 99%
“…Two entries by Kim et al ( 24 , 29 ) applied the sarcopenia index, that is, the ratio of total appendicular skeletal muscle mass (kg) to body mass index (kg/m 2 ), using consistent cutoffs of <0.789 for men and <0.521 for women. Two sarcopenia entries Resulted from muscle deficits estimated by the psoas muscle index of L3 ( 32 , 35 ). Finally, a single prevalence entry was derived from the construct used by ( 37 ), namely, a paraspinal muscle index deficiency, diagnosed on values <12.62 cm 2 /m 2 for men and <9.77 cm 2 /m 2 for women.…”
Section: Resultsmentioning
confidence: 99%
“…Hight prevalence of sarcopenia in our cohort was probably related with LC decompensation in vast majority of patients and >20 MELD in more than two-thirds of patients at baseline. A number of studies have demonstrated an association between LC severity, alcohol-related etiology, male sex, and sarcopenia incidence [2,8,20,32]. In our cohort, the incidence of sarcopenia increased along with the disease stage and reached 86.3 % in CTP C patients.…”
Section: Discussionmentioning
confidence: 48%
“…In another study, low PMI values, independent of MELD, were associated with adverse posttransplant results: infectious complications, prolonged ventilation and intensive care, and higher oneyear mortality [11]. Three studies published this year show that PMI-assessed sarcopenia is associated with reduced survival of LC patients awaiting transplantation and patients who have already undergone transplantation, as well as survival of hepatocellular carcinoma patients receiving immune and targeted anticancer therapy [2,25,35]. Thus, the psoas muscle dimensions were considered a reliable tool for detection of sarcopenia and prediction of short-term survival in LC.…”
Section: Discussionmentioning
confidence: 98%
“…, patients with HCC, at TIPS placement, or post-LT), 17 had insufficient data, and 12 had overlapping cohorts. Finally, 39 studies met the inclusion criteria [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] and were included in the main analysis, representing a total of 12,827 patients. Data from eight additional studies 12 , [55] , [56] , [57] , [58] , [59] , [60] , [61] from the overlapping cohorts were used in the subgroup analyses.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the included studies are shown in Table 1 . Briefly, 19 studies were conducted in Asia, 16 , 18 , [20] , [21] , [22] , [24] , [25] , [26] , [27] , 29 , 31 , 32 , 38 , 39 , 45 , 46 , 48 , 50 , 53 12 studies in Europe, 17 , 19 , 23 , 28 , 34 , 36 , 40 , 41 , 44 , 47 , 49 , 54 six studies in North America, 30 , 33 , 37 , 42 , 43 , 52 one in Latin America (Argentina) 35 and one in Oceania (Australia). 51 Only eight studies were prospective, 16 , 20 , 21 , 23 , 31 , 34 , 37 , 49 and the rest were retrospective.…”
Section: Resultsmentioning
confidence: 99%